If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.4(4x + 11) = 4(1 + -3x) + 14 Reorder the terms: 0.4(11 + 4x) = 4(1 + -3x) + 14 (11 * 0.4 + 4x * 0.4) = 4(1 + -3x) + 14 (4.4 + 1.6x) = 4(1 + -3x) + 14 4.4 + 1.6x = (1 * 4 + -3x * 4) + 14 4.4 + 1.6x = (4 + -12x) + 14 Reorder the terms: 4.4 + 1.6x = 4 + 14 + -12x Combine like terms: 4 + 14 = 18 4.4 + 1.6x = 18 + -12x Solving 4.4 + 1.6x = 18 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 4.4 + 1.6x + 12x = 18 + -12x + 12x Combine like terms: 1.6x + 12x = 13.6x 4.4 + 13.6x = 18 + -12x + 12x Combine like terms: -12x + 12x = 0 4.4 + 13.6x = 18 + 0 4.4 + 13.6x = 18 Add '-4.4' to each side of the equation. 4.4 + -4.4 + 13.6x = 18 + -4.4 Combine like terms: 4.4 + -4.4 = 0.0 0.0 + 13.6x = 18 + -4.4 13.6x = 18 + -4.4 Combine like terms: 18 + -4.4 = 13.6 13.6x = 13.6 Divide each side by '13.6'. x = 1 Simplifying x = 1
| -3/2v-4/7=-8/5 | | 2x-5+6-x-2x=17 | | 150+2p=195-1p | | (-3)+17x-6(-3)=2 | | 3(4x-5)=5(2x-1) | | x=-14+5y | | 5-x+37=50-10 | | 3a+6=-4a+2 | | 12x-21=28(4x-1) | | 12y^9/2y^11 | | 5-9/8x=6 | | X-4+4=-7 | | (y^2-x^2)dy+(2*x*y)dx=0 | | X-4+4=7 | | F(x)=-3(x+3)squared+3 | | 4+16x=10+15x | | 8x+-7=-2x+5 | | 10+3x-x-4=x | | 13x+17+34=90 | | 8x+1+9x-7=180 | | Z-6=z-4 | | -2x-7=32 | | (4+8)n=36 | | (4+8)n=3 | | 10x-14=-2x-13 | | 772x= | | 10x-14=2x+13 | | 5y+39+4x+6=180 | | x(x+2)=1295 | | 9x-15=-5x-16 | | 9x-15=5x+16 | | n-8+3=5 |